Combining PSA and PET features to select candidates for salvage lymph node dissection in recurrent prostate cancer. Issue 1 (4th August 2022) - Bravi, Carlo A.; Heidenreich, Axel; Fossati, Nicola; Gandaglia, Giorgio; Suardi, Nazareno; Mazzone, Elio; Stabile, Armando; Cucchiara, Vito; Osmonov, Daniar; Juenemann, Klaus‐Peter; Karnes, R. Jeffrey; Kretschmer, Alexander; et al.
Abstract: Objective: To evaluate the relationship between pre‐operative PSA value, 68 Ga‐prostate‐specific‐membrane‐antigen (PSMA) PET performance and oncologic outcomes after salvage lymph node dissection (sLND) for biochemical recurrent prostate cancer (PCa). Patients and methods: The study included 164 patients diagnosed with ≤2 pelvic lymph‐node recurrence(s) of PCa documented on 68 Ga‐PSMA PET scan and treated with pelvic ± retroperitoneal sLND at 11 high‐volume centres between 2012 and 2019. Pathologic findings were correlated to PSA values at time of sLND, categorized in early (<0.5 ng/ml), low (0.5–0.99 ng/ml), moderate (1–1.5 ng/ml) and high (>1.5 ng/ml). Clinical recurrence (CR)‐free survival after sLND was calculated using multivariable analyses and plotted over pre‐operative PSA value. Results: Median [interquartile range (IQR)] PSA at sLND was 1.1 (0.6, 2.0) ng/ml, and 131 (80%) patients had one positive spot at PET scan. All patients received pelvic sLND, whereas 91 (55%) men received also retroperitoneal dissection. Median (IQR) number of node removed was 15 (6, 28). The rate of positive pathology increased as a function of pre‐operative PSA value, with highest rates for patients with pre‐operative PSA > 1.5 ng/ml (pelvic‐only sLNDs: 84%; pelvic + retroperitoneal sLNDs: 90%). After sLND, PSA ≤ 0.3 ng/ml was detected in 67 (41%) men. On multivariable analyses, pre‐operative PSA was associated with PSA response ( p  < 0.0001). There were 51 CRs after sLND. After adjusting for confounders, we found a significant, non‐linear relationship between PSA level at sLND and the 12‐month CR‐free survival ( p  < 0.0001), with the highest probability of freedom from CR for patients who received sLND at PSA level ≥1 ng/ml. Conclusions: In case of PET‐detected nodal recurrences amenable to sLND, salvage surgery was associated with the highest short‐term oncologic outcomes when performed in men with PSA ≥ 1 ng/ml. Awaiting confirmatory data from prospective trials, these findings may help physicians to optimize the timing for 68 Ga‐PSMA PET in biochemical recurrent PCa.